El movimiento humano en las láminas proyectivas: una aportación a la III del test de Rorschach - Jiménez Gomez, Fernando (1992)
This paper analyzes the interpretation of human movement (M) that appear in the m Rorschach Inkblot and the Projectives Inkblots. In this sense the Projectives Jnkblots of Dr. Rodrigues Isidoro are one of the most effective measures to discriminate and analyze the mental activity related to movement that appears in the m. Rorschach Inkblot. A eomparative study of two groups of subjects (150 adolescents and 150 adults), without pathological evidence, was carried out. Measures of human movement on the Rorschach Inkblot Test and the Projectives Inkblots were obtained. Comparison of results showed some significant differences in the human contents with movement. Differences were systematically in the M answers in the Rorschach and in the Projectives Inkblots.